A taxonomic revision of the genus Buddleja (Buddlejeae, Scrophulariaceae) in Brazil - Coelho, Guilherme Peres; Miotto, Silvia Teresinha Sfoggia (Phytotaxa, 2018)
In this work, we revise the taxonomy of Buddleja in Brazil. This genus has 16 native and two introduced cultivated and adventitious species in the country. We present here descriptions, distribution and habitat information, flowering and fruiting periods, taxonomic remarks, photographs and propose a conservation status for each species.